2022
DOI: 10.3390/molecules27020393
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antibacterial and Dyeing Potential of Crude Pigment Extract of Gonatophragmium triuniae and Its Chemical Characterization

Abstract: Filamentous fungi synthesize natural products as an ecological function. In this study, an interesting indigenous fungus producing orange pigment exogenously was investigated in detail as it possesses additional attributes along with colouring properties. An interesting fungus was isolated from a dicot plant, Maytenus rothiana. After a detailed study, the fungal isolate turned out to be a species of Gonatophragmium belonging to the family Acrospermaceae. Based on the morphological, cultural, and sequence-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Only nine fungal genera-Aspergillus, Monascus, Chaetomium, Penicillium, Hypoxylon, Muycopron, Phomopsis, Talaromyces, and Pleosporales-had azaphilones had isolated from them [157]. The oldest known source of azaphilone colors is a genus of fungi called Monuscus, which is still regarded as one of the most prolific producers of pigments in modern times [158]. Azaphilones pigments are a category of secondary metabolites produced by Monascus sp.…”
Section: Azaphilonesmentioning
confidence: 99%
“…Only nine fungal genera-Aspergillus, Monascus, Chaetomium, Penicillium, Hypoxylon, Muycopron, Phomopsis, Talaromyces, and Pleosporales-had azaphilones had isolated from them [157]. The oldest known source of azaphilone colors is a genus of fungi called Monuscus, which is still regarded as one of the most prolific producers of pigments in modern times [158]. Azaphilones pigments are a category of secondary metabolites produced by Monascus sp.…”
Section: Azaphilonesmentioning
confidence: 99%
“…After the visualization was carried out, followed by detection using specific reagents with the addition of 2,2-diphenyl-1-picrylhydrazyl (DPPH), vanillin-H2SO4, and FeCL3 reagents. Afterwards, the spot's Rf value was calculated [7,8,9]. In addition, a -carotene was prepared by dissolving it in chloroform.…”
Section: Thin Layer Chromatography (Tlc)mentioning
confidence: 99%
“…Furthermore, a study conducted by Lagashetti et al [9] reported that crude pigment extract of Gonatophragmium triuniae had antioxidant activity. Fungus Monascus purpureus and Penicillium mallochii were also known to produce several pigments with antibacterial and antioxidant properties [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Since the fungal pigments naturally possess antioxidant properties, they have a potential in textile industries reducing the need for the use of coated antioxidants in fabrics (93). Another endophytic fungus, Talaromyces purpureogenus KKP was isolated and characterized from the soil in Keekan village, Kasaragod district, which had good antioxidant activity and lower IC50 value, indicating good potential as a food colorant (112).…”
Section: Antioxidant Activitymentioning
confidence: 99%